Unravelling the hybrid vigor in domestic equids: the effect of hybridization on bone shape variation and covariation - Hanot, Pauline (BMC Evol Biol, 2019)
BACKGROUND: Hybridization has been widely practiced in plant and animal breeding as a means to enhance the quality and fitness of the organisms. In domestic equids, this hybrid vigor takes the form of improved physical and physiological characteristics, notably for strength or endurance. Because the offspring of horse and donkey is generally sterile, this widely recognized vigor is expressed in the first generation (F1). However, in the absence of recombination between the two parental genomes, F1 hybrids can be expected to be phenotypically intermediate between their parents which could potentially restrict the possibilities of an increase in overall fitness. In this study, we examine the morphology of the main limb bones of domestic horses, donkeys and their hybrids to investigate the phenotypic impact of hybridization on the locomotor system. We explore bone shape variation and covariation to gain insights into the morphological and functional expressions of the hybrid vigor commonly described in domestic equids. RESULTS: Our data reveal the occurrence of transgressive effects on several bones in the F1 generation. The patterns of morphological integration further demonstrate that the developmental processes producing covariation are not disrupted by hybridization, contrary to functional ones. CONCLUSIONS: These results suggest that an increase in overall fitness could be related to more flexibility in shape change in hybrids, except for the main forelimb long bones of which the morphology is strongly driven by muscle interactions. More broadly, this study illustrates the interest of investigating not only bone shape variation but also underlying processes, in order to contribute to better understanding how developmental and functional mechanisms are affected by hybridization.